United States. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The Inter-American Institute for Cooperation on Agriculture (IICA) led initiatives at COP28 to increase hemispheric participation in UN COP processes, obtaining external resources to support sustainable agriculture in the Americas. They forged strategic partnerships with Food Tank, the Inter-American Development Bank (IDB), and others. IICA secured resources from the United States Department of Agriculture for agricultural climate actions. They signed general agreements with the World Food Prize Foundation and the Pan American Development Foundation (PADF). In 2023, they participated in the Borlaug Dialogue in Iowa, addressing climate change, water scarcity, and crop diseases. They gave awards to rural leaders, including Krysta Harden and Marilyn Hershey. They advocated for rural women at the UN Commission on the Status of Women. They led the fight against TR4 banana disease and promoted sustainable agricultural practices. They supported impact investing conferences in Miami and facilitated youth leadership in agriculture with the World Food Prize Foundation. Together with Virginia Tech, they produced the first Spanish version of the GAP Report. They strengthened hemispheric cooperation with key partners, such as the USDA, PAHO, the IDB and other organizations.